(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Sodhana chikitsa is an important treatment modality in Ayurveda in which the disease causing morbid Doshas are eliminated through nearest route. Vamana, Virechana, Nasya, Vasthi are the important bio purification measures. Once Doshas are eliminated through Sodhana procedures, it will never produce disease again. Among these Vasthi is considered as important one and known as Ardha chikitsa. Vasthi can be given in various forms according to the condition of disease and patient. By changing the additive drugs and their proportion we can change the effect of Vasthi in our body for the concerned disease different type of Vashti are mentioned in Brihatrayis based on disease and Dosha state. Choorna vasthi also known as Ruksha vasthi is a type of Niruhavasthi mentioned in Chakrapani teeka and is widely practiced nowadays in different clinical scenarios. But there is no direct reference about this Vasthi available in Brihatrayis. This article is to provide an insight on Choorna vasthi used in different conditions by analysing different studies done with it.